HUBUNGAN PEMENUHAN NUTRISI DENGAN STATUS GIZI BALITA YANG DIRAWAT DI WILAYAH PUSKESMAS PANTI KABUPATEN JEMBER - Kustin; Faridha Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
The nutritional status of children is an important thing that must be known by every parent. Poor nutrition fulfillment in children can cause stunted growth and development both physical and psychomotor and mental. The purpose of this study was to determine the relationship of nutritional fulfillment with nutritional status in children under five years old at the Panti Health Center in Jember Regency. This research is a correlation study (correlation study). The population in this study were children under five who were treated in the Panti Puskesmas Area of ​​Jember Regency totaling 76 people. The number of samples was 64 people, the sampling used was simple random sampling. Data were analyzed with chi square. The results showed that most of the nutritional status of toddlers with good nutritional status as many as 57 (89.1%) of respondents, the majority of respondents in fulfilling nutritional needs including those in toddlers were in the good category of 54 (84.4%) respondents. Based on Fisher's Exact Test, the p value is 0.009 <0.05, Ha is accepted. The conclusion of this study is that there is a relationship between nutritional fulfillment and the nutritional status of children under five years of age being treated in the Panti District Health Center in Jember Regency